Anaerobic Microbiota Derived from the Upper Airways Impact Staphylococcus aureus Physiology - Lucas, Sarah K.; Villarreal, Alex R.; Ahmad, Madison M.; Itabiyi, Abayo; Feddema, Erin; Boyer, Holly C.; Hunter, Ryan C. (Infection and immunity, 2021)
Staphylococcus aureus is associated with the development of persistent and severe inflammatory diseases of the upper airways. Yet, S. aureus is also carried asymptomatically in the sinonasal cavity of ∼50% of healthy adults. The causes of this duality and host and microbial factors that tip the balance between S. aureus pathogenesis and commensalism are poorly understood. Staphylococcus aureus is associated with the development of persistent and severe inflammatory diseases of the upper airways. Yet, S. aureus is also carried asymptomatically in the sinonasal cavity of ∼50% of healthy adults. The causes of this duality and host and microbial factors that tip the balance between S. aureus pathogenesis and commensalism are poorly understood. We have shown that by degrading mucins, anaerobic microbiota support the growth of airway pathogens by liberating metabolites that are otherwise unavailable. Given the widely reported culture-based detection of anaerobes from individuals with chronic rhinosinusitis (CRS), here we tested our hypothesis that CRS microbiota is characterized by a mucin-degrading phenotype that alters S. aureus physiology. Using 16S rRNA gene sequencing, we indeed observed an increased prevalence and abundance of anaerobes in CRS relative to non-CRS controls. PICRUSt2-based functional predictions suggested increased mucin degradation potential among CRS microbiota that was confirmed by direct enrichment culture. Prevotella , Fusobacterium , and Streptococcus comprised a core mucin-degrading community across CRS subjects that generated a nutrient pool that augmented S. aureus growth on mucin as a carbon source. Finally, using transcriptome sequencing (RNA-seq), we observed that S. aureus transcription is profoundly altered in the presence of mucin-derived metabolites, though expression of several key metabolism- and virulence-associated pathways varied between CRS-derived bacterial communities. Together, these data support a model in which S. aureus metabolism and virulence in the upper airways are dependent upon the composition of cocolonizing microbiota and the metabolites they exchange.